Morphological evaluation of cork oak (Quercus suber): Mediterranean provenance variability in Tunisia - Gandour, M.; Khouja, M. L.; Toumi, L.; Triki, S. (Annals of forest science, 2007)
Twenty-six provenances (2 340 plants) of cork oak (Quercus suber spp.) originating from Portugal, Spain, Italy, Morocco, Algeria, and Tunisia were tested for genetic variation among and within provenances by growth traits. Seven morphometrical characters were measured in 90 plants from each provenance. Analysis of variance showed highly signiﬁcant diﬀerences for all characters. The phenotypic coeﬃcient of diﬀerentiation reached 0.24 for the form and 0.22 for height, thus revealing a strong structuring between the provenances. Comparative study of growth among the provenances revealed more vigorous growth and better survival rate for those from Morocco, Spain, and Portugal, which may constitute better materials for aﬀorestation. Furthermore, this variability appeared to be geographically structured and would be mainly genetically controlled, as cork oak provenances were cultivated under the same environmental conditions. Our results should be helpful for guide forest managers in aﬀorestation.
Keywords: aforestation; Genetic variability; Mediterranean plants; Quercus suber

Ecophysiological Traits Associated with Drought in Mediterranean Tree Seedlings: Individual Responses versus Interspecific Trends in Eleven Species - Valladares, F.; Sánchez-Gómez, D. (Plant Biology, 2006)
Abstract: Species differ regarding their drought tolerance and individuals of a given species can modify their morphology and physiology in response to drought. However, since evolutionary and ecological selective pressures differ, individual and interspecific responses to drought might not match. We determined summer survival and a number of ecophysiological variables in two factorial experiments with seedlings of eleven tree species present in Mediterranean ecosystems, grown under slowly imposed water stress and control conditions. Plants experiencing drought exhibited reduced growth, low specific leaf area, chlorophyll content, and photosynthetic rate when compared to the controls, and species-specific drought tolerance was associated with an analogous set of trait values. However, while species with high leaf area ratio and shoot-root ratio exhibited greater drought tolerance, drought induced the reversed response within species. Contrary to expectations, water use efficiency was lower in drought-tolerant species and decreased in water-stressed individuals compared to the control plants. There was a distinctive phylogenetic signal in the functional grouping of species, with oaks, pines, and other genera being clearly different from each other in their drought tolerance and in their functional responses to drought. However, all relationships between ecophysiological variables and drought tolerance were significant after accounting for phylogenetic effects, with the exception of the relationship between drought tolerance and photochemical efficiency. Our results show that drought tolerance is not achieved by a single combination of trait values, and that even though evolutionary processes and individual responses tend to render similar results in terms of functional traits associated with drought, they do not necessarily match.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Drought tolerance; functional traits; Mediterranean plants; phylogeny; water use efficiency; woody seedlings